A review on characteristics and potential applications of henna leaves (lawsonia inermis) - Thana Singam, Rupashinii; Marsi, Noraini; Abdul Rashid, Azrin Hani; Nasir, Siti Hana; Ibrahim, Siti Aida; Roslan, Mohd Nazrul; Huzaisham, Nur Athirah; Mohd Fodzi, Muhammad Haikal (American Scientific Publishers, 2020)
This review paper reports the studies available on the characteristics and applications of the henna (Lawsonia inermis) as a natural dye. Textile materials are mainly from synthetic dyes and fibers which are not renewable and not biodegradable. Around 30 million of tonnes was estimated for the global consumption of textiles and was expected to grow up to 3% per annum while 70,000 tonnes of dyes were released to the environment. The population of people who will have allergic to the chemicals will grow up to 60% by year 2020 which was stated in business week. Apart from that, natural dyes can be extracted and process from various sources such as plants, leaves, minerals, roots, barks and insect sections. Plants that was found in the world approximately 20% were for the pharmaceutical or biological test and new antibiotics were introduced in the market are obtain from natural or semi-synthetic resources. For the biological test, henna oil was tested against Staphylo-coccus aureus which was 870 g/mL and Neisseria gonorrhoeae was 87 g/mL respectively while henna leaves extraction using methanol of 95% showed significant in-vitro antihyperglycemic effect. Chemical contains in the henna are carbohydrates as 33.62%, fibers as 33.5%, fatty oils as 10–11% and essential oil as 0.01–0.02%. Moreover, the good UV absorbency for the henna dyed cotton was at 900 C for 60 minutes and the colour fastness for the fabric which was dyed with henna is 4 which is good. Henna dye has slightly negative charge for the higher pH 9 for the washing fastness. The optimize condition for the pre-mordant is 4% for the copper sulphate (CuSO4) for cotton with the extraction of henna leaves. Furthermore, the optimum condition for the henna to remove lead Pb (II) from wastewater are pH 6, contact time is 80 minutes, 10 ppm for the initial metal concentration and 0.75 g/L for adsorbent dosage.